Protective Effects of Platycodin D on Lipopolysaccharide-Induced Acute Lung Injury by Activating LXRα–ABCA1 Signaling Pathway - Hu, Xiaoyu; Fu, Yunhe; Lu, Xiaojie; Zhang, Zecai; Zhang, Wenlong; Cao, Yongguo; Zhang, Naisheng (Frontiers in Immunology, 2017)
The aim of this study was to investigate the effect of Platycodin D (PLD) on LPS-induced acute lung injury and clarify the possible mechanism. An LPS-induced mouse acute lung injury model was used to confirm the anti-inflammatory activity of PLD in vivo. The A549 lung epithelial cells were used to investigate the molecular mechanism and targets of PLD in vitro. In vivo, the results showed that PLD significantly attenuated lung histopathologic changes, myeloperoxidase (MPO) activity, and pro-inflammatory cytokines levels, including TNF-α, IL-1β and IL-6. In vitro, PLD inhibited LPS-induced IL-6 and IL-8 production in LPS-stimulated A549 lung epithelial cells. Western blot analysis showed that PLD suppressed LPS-induced NF-κB and IRF3 activation. Moreover, PLD did not act though affecting the expression of TLR4. We also showed that PLD disrupted the formation of lipid rafts by depleting cholesterol and prevented LPS-induced TLR4 trafficking to lipid rafts, thereby blocking LPS-induced inflammatory response. Finally, PLD activated LXRα-ABCA1-dependent cholesterol efflux. Knockdown of LXRα abrogated the anti-inflammatory effects of PLD. The anti-inflammatory effects of PLD was associated with up-regulation of the LXRα-ABCA1 pathway, which resulted in disrupting lipid rafts by depleting cholesterol and reducing translocation of TLR4 to lipid rafts.